Testing the influence of pornography on sexual violence in Croatia: the public crime statistics approach - Landripet, Ivan (2005)
Worldwide research of the effects of pornography use on attitudes and behavior has predominantly been of the microscopic and experimental nature, with considerably less studies based upon “macro” perspectives and involving mid-range theories. One such approach focuses on the dynamics of sex crime during a time span sufficiently long to cover transition from pornographic scarcity to abundance of easily available sexually explicit material (the dynamics of sexual crime is controlled by the dynamics of the comparable non-sexual crime). This paper implements “the public crime statistics approach” to the case of Croatia. The time range of tracking and comparing temporal trends of the aggravated sexual and non-sexual crime (rape and sexual assault versus murder and assault) spans from 1978, through 2003. Comparable to all the national studies conducted so far, the results do not support the notion of significant and independent increase in sex crime conditioned by the increase in pornography availability, but rather indicate (in the case of Croatia) certain structural causes that determine somewhat matching trends both of sexual and non-sexual violence.
ENG